Factors Affecting Anaerobic Digestion Efficiency to Produce Biogas - Srivichai, Piyavadee; Rodsrida, Chumaporn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2020)
Under the energy crisis, searching for the source of renewable energy plays an important role nowadays. Especially, biogas as the renewable energy generated from the anaerobic digestion process of various biomass and organic wastes. Due to biogas is clean renewable energy and environmentally friendly, it can be used beneficially in many ways such as heating, transportation, lighting, and electrical production. Thus, to obtain a qualified biogas from an efficient anaerobic digestion process, this paper is interested in reviewing several factors such as pH, carbon to nitrogen ratio, organic loading rate, retention time, moisture, total solids, nutrient, mixing, and volatile fatty acids to alkalinity ratio, etc. These factors are the vital factors influencing the biogas production efficiency. Moreover, it can be used as the basic guideline for considering the anaerobic digestion application to produce further biogas as a renewable energy.